Shelf-Life Extension of Large Yellow Croaker (Larimichthys crocea) Using Active Coatings Containing Lemon Verbena (Lippa citriodora Kunth.) Essential Oil - Li, Bo; Wang, Xuesong; Gao, Xin; Ma, Xuan; Zhang, Leilei; Mei, Jun; Xie, Jing (Frontiers in Nutrition, 2021)
This study was to investigate the effect of locust bean gum (LBG) and sodium alginate (SA) active coatings containing Lemon verbena (Lippa citriodora Kunth.) essential oil (LVEO) emulsions on microbiological, physicochemical and organoleptic evaluation of large yellow croaker (Larimichthys crocea) samples during 18 days storage at 4 oC. Results showed that LBG/SA coatings combining with 0.30 % or 0.60 % LVEO emulsions could significantly lower total viable count (TVC), Pseudomonas spp., H2S-producing bacteria, lactic acid bacteria and psychrophilic counts, and reduce the productions of off-flavor compounds including the trimethylamine (TMA), total volatile basic nitrogen (TVB-N) and ATP-related compounds, and accumulation of free fat acids (FFAs). Further, LBG/SA coatings containing LVEO emulsions could more efficiently retard the water migration by magnetic resonance imaging (MRI) results, and maintained quality of large yellow croaker during storage at 4 oC according to organoleptic evaluation results.